Progress, challenges and opportunities for Red Listing. (June 2019) - Bachman, Steven P.; Field, Richard; Reader, Tom; Raimondo, Domitilla; Donaldson, John; Schatz, George E.; Lughadha, Eimear Nic
Abstract: Despite its recognition as an important global resource for conservation, the International Union for Conservation of Nature's (IUCN) Red List of Threatened Species only provides assessments of extinction risk for a small and biased subset of known biodiversity. A more complete Red List can better support species-level conservation by indicating how quickly we need to act on species deemed to be priorities for conservation action. Vascular plants represent one of the Red List knowledge gaps, with only 7% of species currently on the Red List (including in the Data Deficient and Least Concern categories). Using vascular plants as a case study we highlight how recent developments, such as changes to rules, improvements to data management systems, better assessment tools and training, can support Red List assessment activity. We also identify ongoing challenges, such as the need to support regional and national assessment initiatives, the largely voluntary nature of the Red List community, as well as the need to meet core operating costs for the Red List. Finally, we highlight how new opportunities such as automation and batch uploading can fast-track assessments, and how better monitoring of assessment growth can help assess the impact of new developments. Most of our findings are also applicable to other species-rich groups that are under-represented on the Red List. We examine trends in plant Red Listing and conclude that the rate of new assessments has not increased in line with what would be required to reach goals such as the Barometer of Life. This may result partly from a lag between recent changes and their effects, but further progress can be made by realising the opportunities outlined here and by growing the Red List community and strengthening collaboration with IUCN. Highlights: The IUCN Red List, a key conservation resource, has incomplete and biased coverage. Most known species have yet to be assessed and published on the Red List. Rule changes and technical innovations may help scale up production of assessments Current assessment rates are not sufficient to meet 2020 targets